Work under neoliberalism: subcontracting at a chilean state university (Polis (Santiago), 2019)
The characteristics of the subcontracted work of hygiene personnel in a Chilean state university are presented. With a convergent mixed research design, the findings show high levels of psychosocial risk in the SUSESO/ ISTAS21 questionnaire, in addition to the following discursive categories: (1) problems of economic income, (2) loss of control over the labor relationship, (3) demands and low institutional support, (4) exercise of labor rights, (5) individual responsibility and uncertainty in the construction of the life project. It is concluded that labor subcontracting produces precariousness and segmentation of the work group, negatively affecting the health and subjectivity of the workers.
Keywords: Subcontract; state university; unskilled workers; precarious work; women; psychosocial risk; work sociology